2020
DOI: 10.1007/978-3-030-44578-2_1-1
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of Underutilized Vegetables and Legumes

Abstract: Plants existing in nature could be used as source of nutrition and bioactive compounds. Some of the wild and underutilized plants such as African baobab, amaranth, tarragon, Malabar spinach, borage, Ethiopian rape, goosefoot, chicory, spider plant, mallow, sea kale, curcuma, squash, roselle, water spinach, bitter melon, drumstick, tassel hyacinth, prickly pear, parsnip, tomatillo, Indian poke, purslane, yellow cresses, black nightshade, and water leaf are used as vegetables, and some other wild leguminous plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 110 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…Wild resources are an essential part of biocultural heritage for all cultures, which have used them for centuries ( Rotherham, 2015 ; Tanús et al, 2019 ). Within these resources, the plants are a vital support in extreme environmental conditions and threatened habitats, as they possess many health-promoting values ( Murthy & Paek, 2020 ). It has been widely observed ( De Cortes Sánchez-Mata & Tardío, 2016 ) that the Mediterranean macrobioclimate and its ecosystems show remarkably high diversity in the heterogeneity of their plants.…”
Section: Introductionmentioning
confidence: 99%
“…Wild resources are an essential part of biocultural heritage for all cultures, which have used them for centuries ( Rotherham, 2015 ; Tanús et al, 2019 ). Within these resources, the plants are a vital support in extreme environmental conditions and threatened habitats, as they possess many health-promoting values ( Murthy & Paek, 2020 ). It has been widely observed ( De Cortes Sánchez-Mata & Tardío, 2016 ) that the Mediterranean macrobioclimate and its ecosystems show remarkably high diversity in the heterogeneity of their plants.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the nutritional components of legumes, they have been attributed to pharmacological roles due to the presence of important bioactive compounds. Studies have shown that phytochemicals found in underutilized legumes have antioxidant, anticancer, antidiabetic, antihypertensive, anti-inflammatory, antimicrobial, and hepatoprotective activities [47,48]. However, many people are unaware of the health advantages of their phytochemicals, therefore they have yet to be fully utilized for improved health and well-being.…”
Section: Nutrient Content and Health Benefits Of Underutilized Legumesmentioning
confidence: 99%
“…A direct bioactive compound content or functionality comparison between different leguminous species was not provided, and similarities between species were not discussed [23,24]. The only review that included a comparison between species focused on vegetables and did not discuss soybean, chickpea, and pea [25].…”
Section: Introductionmentioning
confidence: 99%